Kepemimpinan Efektif Leadership in Digital Transformation Era - Bowo Widiharto; Nunung Nurchayatun; Ronald Hidayat Marikar (Syntax Corporation Indonesia, 2023)
Leadership plays an important role in the organization. The success or failure of an organization is determined by the resources that exist within the organization. In addition, the factor that plays an important role is the leadership factor. An effective leader must have the courage to make decisions and take responsibility for the consequences and risks that arise as a consequence of the decisions he makes. The main role of leadership is to influence others to achieve the goals that have been set. This study used a qualitative literature review method. The use of literature has various purposes based on the type of qualitative research conducted. In general, to maintain the naturalness of the data, extensive use of literature was made after the research was conducted. The definition of leadership according to Moejiono is the result of one direction which may be because the leader has certain qualities that make him superior among his followers. In directing and motivating